A gradient polisher and its preparation method and application

CN122917482APending Publication Date: 2026-10-16SHANGHAI REINPHEN NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611061074.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-16
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0008]现有技术中大部分研磨子是均质复合材料,且大部分属于非微孔材料,研磨子普遍存在散热性较差,边缘强度低,边缘容易发生崩角、掉块、脱落,研磨子芯部容易产生金属镶嵌等问题

Benefits of technology

(1)通过优化配方原材料组合,合理设置配比,结合特殊生产工艺制得梯度研磨子,梯度研磨子为微孔材料,芯部密度最低,孔隙率最大,散热较好,能够降低摩擦温度,避免金属镶嵌的产生。梯度研磨子耐热性较高,磨耗低,使用寿命大大提高,粘着系数提高了11-67%,修形效果提高了25%-50%,增粘、修形效果得到极大的提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to a kind of gradient abrasive and its preparation method and application.The preparation method includes the following steps: proportionally adding the component raw material of preparing gradient abrasive into high-speed mixer and mixing stirring, to obtain mixture;Mixed material and steel back are placed in porous mold, and molding is formed, to obtain gradient abrasive blank;After demolding, gradient abrasive blank is heated and solidified, finally machining is obtained gradient abrasive.Compared with prior art, the gradient abrasive of the present application has faster heat dissipation, can reduce friction temperature, avoid metal inlay generation, has higher heat resistance, lower wear, greatly improves service life;Better tackifying, shaping effect;The performance of different positions gradually presents gradient change, gradually increases from core to edge, gradually increases in strength, the strength of periphery edge is highest, prevent the phenomenon of collapse angle, block drop;Material has higher strength and hardness;Product noise and thermal decay are reduced;Product is easier to form and process;Production efficiency is higher and the like advantages.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of tread cleaning technology for high-speed rail and urban rail vehicles, and in particular relates to a gradient abrasive, its preparation method and application. Background Technology

[0002] The grinding wheel is a key component of the tread cleaning device on high-speed rail and urban rail vehicles. It functions to clean, increase adhesion, and reshape the wheel, effectively utilizing the adhesion coefficient between the wheel and rail to ensure good wheel surface condition, shorten braking distance, and prevent wheel slippage and wheel idling. The grinding wheel also prevents the wheel from developing polygonal shapes, avoiding wheel out-of-roundness issues and ensuring safe train operation.

[0003] Patent CN112810575A discloses a grinding element for a tread cleaning device on urban rail vehicles and its preparation method. The friction body, by weight percentage, comprises 5%–11% binder, 12%–24% tackifier, 15%–22% shaping agent, 12%–36% reinforcing fiber, and 16%–56% modifier. It uses modified phenolic resin as the binder, employs an organosilicon-modified resin with better moisture and heat resistance, selects tackifiers with strong adhesion such as zinc oxide and kaolin, combines low-hardness and medium-hardness abrasives to increase the particle size difference of hard particles, uses fibrous materials such as sepiolite fiber, and adjusts the shape and size of the grinding element to adapt to the polygonal wavelength of urban rail wheels. This solution improves the braking effect of urban rail vehicles, extends the life of the grinding element, increases the wheel-rail adhesion coefficient, reduces low-point wear of the wheel, avoids scratches and peeling, and improves wheel shaping efficiency and mechanical performance.

[0004] Patent CN118834498A discloses an abrasive and its preparation method. The abrasive is made of the following materials, with each component comprising the following weight percentages: binder 10%-22%, tackifying filler 15%-40%, shaping filler 15%-30%, reinforcing fiber 8%-20%, and performance modifier 8%-15%. Using modified aramid fiber, rubber-modified phenolic resin, modified filler, and performance modifier, a high-strength, low-friction-noise abrasive is prepared through silane coupling agent-modified fiber, ball milling co-activation, hot pressing, and variable-temperature curing processes. This method improves the performance of the abrasive in terms of metal embedding, crack chipping, wheel shaping, and friction noise, while minimizing damage to the wheel tread and reducing the likelihood of thermal cracking and severe wavy, furrowed wear.

[0005] Most of the synthetic material abrasives currently available on the domestic market are homogeneous composite materials, and most of them are non-microporous materials. These abrasives generally have poor heat dissipation, low edge strength, and are prone to chipping, breaking, and falling off at the edges. They are also prone to metal embedding in the core, which greatly shortens the service life of the abrasives.

[0006] Functionally graded materials (FCTs) are novel composite materials composed of two or more materials with continuously varying compositions and structures. They were developed to meet the needs of high-tech industries such as modern aerospace, aiming to ensure normal operation under extreme conditions. From a structural perspective, FCTs differ from homogeneous materials and composite materials. They involve selecting two (or more) materials with different properties and continuously altering their composition and structure until the interface disappears, resulting in a slow change in material properties as the composition and structure change.

[0007] However, the overall performance of existing grinding tools cannot simultaneously meet the following requirements: high heat resistance, low wear, good adhesion and shaping effect, high material strength and hardness, reduced product noise and thermal decay, easier product molding and processing, and high production efficiency; the performance gradually changes in different positions, with density gradually increasing and strength gradually increasing from the core to the edge, and the highest strength at the four edges, to prevent corner chipping and breakage. Summary of the Invention

[0008] Most existing abrasives are made of homogeneous composite materials, and most are non-microporous. These abrasives generally suffer from poor heat dissipation, low edge strength, and are prone to chipping, breakage, and detachment at the edges. Furthermore, the core of the abrasive is prone to metal embedding. To address these technical problems, this invention provides a gradient abrasive, its preparation method, and its applications.

[0009] The gradient abrasive prepared by this invention is made of microporous material with high porosity, resulting in rapid heat dissipation, reduced friction temperature, and prevention of metal embedding. The properties of the abrasive prepared by this invention exhibit a gradual gradient change, with density and strength increasing progressively from the core to the edges, reaching the highest strength at the perimeter, thus preventing chipping and breakage. The gradient abrasive prepared by this invention also exhibits high heat resistance, low wear, significantly extended service life, and good adhesion and shaping effects.

[0010] The objective of this invention can be achieved through the following technical solutions: This invention provides a gradient abrasive tribological material, prepared from the following components by mass content: Aromatic alcohol phenolic resin 9%-15% Bismaleimide modified phenolic resin 8%-13% Styrene-butadiene rubber 5%-12% EPDM rubber 7%-14% Potassium hexatite whiskers 7%-12% Sisal fiber 6%-10% Flake graphite 5%-8% 5%-10% silica Hollow bead floats 2%-6% Potassium feldspar 5%-10% Diatomaceous earth 3%-7% zeolite 2%-6% Dolomite 5%-9%.

[0011] In one embodiment of the present invention, the particle size of the silica is 10-50 nm.

[0012] In one embodiment of the present invention, the hollow microspheres have a particle size of 100-200µm.

[0013] In one embodiment of the present invention, the density of the zeolite is 1.9-2.4 g / cm³. 3 Hardness 3-3.5.

[0014] The present invention further provides a method for preparing a gradient abrasive, comprising the following steps: S1. Add the raw materials for preparing the gradient abrasive friction material to a high-speed mixer according to the proportion and mix them to obtain a mixture; S2. Place the mixture and steel backing into a porous mold and press them to form a gradient grinding blank. S3. After demolding, the gradient abrasive blank is heated and cured, and finally machined to obtain the gradient abrasive. The steel backing serves to fix the friction material of the abrasive.

[0015] In one embodiment of the present invention, in step S1, the components and their amounts in preparing the gradient abrasive friction material are as follows: 9%-15% aromatic phenolic resin, 8%-13% bismaleimide modified phenolic resin, 5%-12% styrene-butadiene rubber, 7%-14% ethylene propylene diene monomer (EPDM) rubber, 5%-8% flake graphite, 5%-10% silica, 2%-6% hollow cenospheres, 5%-10% potassium feldspar, 3%-7% diatomaceous earth, 2%-6% zeolite, 5%-9% dolomite, 7%-12% potassium hexatite whiskers, and 6%-10% sisal fiber.

[0016] In one embodiment of the present invention, in step S1, the specific process of preparing the mixture is as follows: aromatic phenolic resin, bismaleimide modified phenolic resin, styrene-butadiene rubber, ethylene propylene diene monomer rubber, flake graphite, silica, hollow cenospheres, potassium feldspar, diatomaceous earth, zeolite and dolomite are added to a high-speed mixer and mixed for 20-35 minutes according to the proportion, and then potassium hexatitanate whiskers and sisal fibers are added according to the proportion and stirred for 20-25 minutes until uniform to obtain the mixture.

[0017] In one embodiment of the present invention, the specific process of compression molding in step S2 is as follows: the mixture and the steel backing are placed into the grinding die. The die is heated from top to bottom and from all sides. The temperature in the middle of the die is 100-180°C, and the temperature around the die is 120-200°C. The temperature around the die is higher than the temperature in the middle of the die. The molding pressure is 20-40 MPa. After the die is closed and pressurized for 60 seconds, the first venting is performed. The pressure is held for 75 seconds for the second venting, then held for 60 seconds for the third venting, then held for 45 seconds for the fourth venting, then held for 30 seconds for the fifth venting, and finally held for 16-20 minutes to obtain the gradient grinding die blank.

[0018] In step S2, during the compression molding process, the upper die head of the grinding die is arc-shaped, higher in the middle and lower around the edges. When pressure is applied, the upper die head extrudes the mixture, pushing it from the center outwards. The denser mixture flows outwards first, and due to the higher temperature at the edges, the mixture solidifies first. With repeated degassing, the upper die head is raised and lowered repeatedly. After repeated extrusion of the mixture, it gradually flows from the center outwards. Combined with the fluid components in the formula, a gradient material is gradually formed. In one embodiment of the invention, in step S3, the specific process of heating and curing is as follows: After demolding, the gradient grinding blank is placed in a curing oven for heating and curing. The heating and curing procedure is as follows: Maintain a curing temperature of 150℃ and a curing time of 2-3 hours; Then the temperature is increased from 150℃ to 180℃, and this heating process takes 60 minutes; Maintain a curing temperature of 180℃ and a curing time of 4-5 hours; The temperature was increased from 180℃ to 210℃, and the heating process took 60 minutes. Maintain a curing temperature of 210℃ and a curing time of 5-6 hours; The temperature was increased from 210℃ to 250℃, and the heating process took 60 minutes. Maintain a curing temperature of 250℃ and a curing time of 8-10 hours.

[0019] The present invention further provides a gradient abrasive prepared by the above-described method, wherein the properties of the gradient abrasive gradually change at different locations, with density gradually increasing and strength gradually increasing from the core to the edge. The gradient abrasive is a gradient functional material.

[0020] The present invention further provides the application of gradient abrasives, which are used to prepare tread cleaning devices for high-speed rail and urban rail vehicles.

[0021] The present invention further provides a tread cleaning device for high-speed rail and urban rail vehicles, which includes the gradient abrasive of the present invention.

[0022] Compared with the prior art, the present invention has the following beneficial effects: (1) By optimizing the combination of raw materials in the formula and setting the ratio reasonably, and combining with special production process, gradient abrasives are made. Gradient abrasives are microporous materials with the lowest core density and the highest porosity. They have good heat dissipation, which can reduce the friction temperature and avoid the formation of metal embedding. Gradient abrasives have high heat resistance, low wear, and greatly improved service life. The adhesion coefficient is increased by 11-67%, and the shaping effect is improved by 25%-50%. The adhesion and shaping effects are greatly improved.

[0023] (2) During the pressing process, the mold adopts a top-bottom and perimeter heating method. Compared with the center of the mold, there are more heating pipes around the perimeter, and the temperature around the perimeter is higher than that in the center. The upper die head of the grinding die is arc-shaped, with a higher center and a lower perimeter. When pressure is applied, the upper die head of the mold extrudes the mixture, pushing it from the center to the perimeter. The denser mixture flows to the perimeter first, and due to the higher temperature at the perimeter, the mixture solidifies first. With repeated venting, the upper die head of the mold will be raised and lowered repeatedly. After repeated extrusion of the mixture, it will gradually flow from the center to the perimeter. At the same time, flowability components are added to the formula. Combined with this special production process, a gradient material is gradually formed.

[0024] (3) The performance of the gradient abrasive prepared by the present invention gradually changes at different positions. From the core to the edge, the density gradually increases and the strength gradually increases, with the highest strength at the four edges, to prevent chipping and breakage.

[0025] (4) Adding aromatic phenolic resin and bismaleimide-modified phenolic resin to the material improves the heat resistance of the phenolic resin, thereby enhancing the wear resistance of the material. The mixed use of different fibers plays a role in hybrid reinforcement and complementarity, improving the strength of the material. Adding raw materials with small particles, large surface area, and good fluidity, such as silica and hollow cenospheres, makes the product have good fluidity during pressing and curing, making the product easier to mold and process. Adding diatomaceous earth and zeolite with loose and porous structure and strong adsorption capacity can reduce product noise and heat decay. It can also increase the strength and hardness of the material, while improving the friction coefficient and wear resistance of the material.

[0026] (5) Using a multi-hole mold for pressing, multiple grinding balls can be produced at once, greatly improving production efficiency. Detailed Implementation

[0027] The present invention will now be described in detail with reference to specific embodiments. These embodiments are based on the technical solution of the present invention and provide detailed implementation methods and specific operating procedures. However, the scope of protection of the present invention is not limited to the following embodiments.

[0028] This invention provides a gradient abrasive tribological material, prepared from the following components by mass content: Aromatic alcohol phenolic resin 9%-15% Bismaleimide modified phenolic resin 8%-13% Styrene-butadiene rubber 5%-12% EPDM rubber 7%-14% Potassium hexatite whiskers 7%-12% Sisal fiber 6%-10% Flake graphite 5%-8% 5%-10% silica Hollow bead floats 2%-6% Potassium feldspar 5%-10% Diatomaceous earth 3%-7% zeolite 2%-6% Dolomite 5%-9%.

[0029] The present invention also provides a method for preparing a gradient abrasive, comprising the following steps: S1. Add the raw materials for preparing the gradient abrasive friction material to a high-speed mixer according to the proportion and mix them to obtain a mixture; S2. Place the mixture and steel backing into a porous mold and press them to form a gradient grinding blank. S3. After demolding, the gradient abrasive blank is heated and cured, and finally machined to obtain the gradient abrasive. The steel backing serves to fix the friction material of the abrasive.

[0030] The precipitated silica has a particle size of 10-50 nm. The hollow cenospheres have a particle size of 100-200 µm. The zeolite has a density of 1.9-2.4 g / cm³. 3 Hardness 3-3.5.

[0031] In step S1, the specific process for preparing the mixture is as follows: aromatic phenolic resin, bismaleimide modified phenolic resin, styrene-butadiene rubber, ethylene propylene diene monomer rubber, flake graphite, silica, hollow cenospheres, potassium feldspar, diatomaceous earth, zeolite, and dolomite are added to a high-speed mixer and mixed for 20-35 minutes according to the proportion. Then, potassium hexatitanate whiskers and sisal fibers are added according to the proportion and stirred for 20-25 minutes until uniform to obtain the mixture.

[0032] In step S2, the specific process of compression molding is as follows: the mixture and steel backing are placed into the grinding die. The die is heated from top to bottom and from all sides. The temperature in the middle of the die is 100-180℃, and the temperature around the die is 120-200℃. The temperature around the die is higher than the temperature in the middle of the die. The molding pressure is 20-40MPa. After the die is closed and pressurized for 60s, the first venting is performed. The pressure is held for 75s for the second venting, then held for 60s for the third venting, then held for 45s for the fourth venting, then held for 30s for the fifth venting, and finally held for 16-20min to obtain the gradient grinding die blank.

[0033] In step S2, during the compression molding process, the upper die head of the grinding mold is arc-shaped, higher in the middle and lower around the edges. When pressure is applied, the upper die head extrudes the mixture, pushing it from the center outwards. The denser mixture flows outwards first, and due to the higher temperature at the edges, the mixture solidifies first. With repeated degassing, the upper die head is raised and lowered multiple times. After repeated compression of the mixture, it gradually flows from the center outwards. Combined with the flowable components in the formula, a gradient material is gradually formed.

[0034] In step S3, the specific process of heating and curing is as follows: after demolding, the gradient-grind blank is placed in a curing oven for heating and curing. The heating and curing procedure is as follows: Maintain a curing temperature of 150℃ and a curing time of 2-3 hours; Then the temperature is increased from 150℃ to 180℃, and this heating process takes 60 minutes; Maintain a curing temperature of 180℃ and a curing time of 4-5 hours; The temperature was increased from 180℃ to 210℃, and the heating process took 60 minutes. Maintain a curing temperature of 210℃ and a curing time of 5-6 hours; The temperature was increased from 210℃ to 250℃, and the heating process took 60 minutes. Maintain a curing temperature of 250℃ and a curing time of 8-10 hours.

[0035] Functions of each ingredient: Bismaleimide-modified phenolic resin has excellent heat resistance and a very high thermal decomposition temperature, and the material does not exhibit high-temperature thermal degradation.

[0036] Aromatic phenolic resin has good heat resistance, with a thermal decomposition temperature of up to 450℃; it has low water absorption, which is beneficial for stabilizing the coefficient of friction and maintaining material strength; it has high bonding strength, good compression molding process, and the resulting products are noiseless and have low wear rate.

[0037] Potassium hexatite whiskers have a high melting point and thermal stability, enabling them to withstand high-temperature environments and improve the thermal stability of materials. They also have excellent wear resistance, which improves the service life and fatigue characteristics of materials.

[0038] Sisal fiber is characterized by its fine, long fibers, strength, wear resistance, and corrosion resistance. It is a high-quality natural fiber, a renewable resource, and can be naturally degraded. It has excellent friction performance and unique physical and chemical properties, representing a green and sustainable development trend.

[0039] Silica, as a filler, is advantageous due to its small particle size, large surface area, and uniform particle distribution. This uniform shape and distribution result in smaller gaps between silica particles, reducing the likelihood of particle accumulation and adhesion. It also exhibits good flowability, making products easier to mold and process. Furthermore, it can increase the hardness, strength, heat resistance, and wear resistance of materials, thereby improving product quality. Silica particle size ranges from 10-50 nm.

[0040] Hollow microspheres are thin-walled, hollow microspheres with fine, hollow, lightweight, high strength, and wear resistance. They also have good flowability and a particle size of 100-200µm.

[0041] Diatomaceous earth, as a filler for friction materials, has a loose and porous structure, strong adsorption capacity, and good heat resistance, which can effectively reduce friction noise and product thermal degradation.

[0042] Zeolite is a natural mineral with a porous structure and a density typically between 1.9 and 2.4 g / cm³. 3 With a hardness of 3-3.5, it has good adsorption properties and chemical stability, and can be used as a filler for friction materials to increase the strength and hardness of the materials, while improving the friction coefficient and wear resistance.

[0043] Unless otherwise specified, all raw materials used in this invention are commercially available in the field, and the equipment used is conventional equipment in the field.

[0044] Example 1 Preparation of raw materials for gradient abrasive friction materials: Aromatic alcohol phenolic resin 9% 13% bismaleimide modified phenolic resin 5% styrene-butadiene rubber 10% EPDM rubber Potassium hexatite whiskers 7% Sisal fiber 9% 5% flake graphite 10% silica Hollow beads 6% Potassium feldspar 10% 3% diatomaceous earth 5% zeolite Dolomite 8% A method for preparing a gradient abrasive includes the following steps: (1) Add aromatic phenolic resin, bismaleimide modified phenolic resin, styrene-butadiene rubber, ethylene propylene diene monomer rubber, flake graphite, silica, hollow cenospheres, potassium feldspar, diatomaceous earth, zeolite and dolomite into a high-speed mixer and mix for 20 minutes. Then add potassium hexatitanate whiskers and sisal fiber in proportion and mix for 25 minutes until uniform to obtain the mixture.

[0045] (2) The mixture and steel backing are placed in a porous mold. The temperature in the middle of the mold is 100℃, and the temperature around the mold is 120℃. The molding pressure is 35MPa. After the mold is closed and pressurized for 60s, the first venting is performed. The pressure is held for 75s for the second venting, then held for 60s for the third venting, then held for 45s for the fourth venting, then held for 30s for the fifth venting, and finally held for 16min to obtain a gradient grinding blank. The upper die head of the grinding blank mold is arc-shaped, high in the middle and low around the edges. When pressure is applied, the upper die head of the mold squeezes the mixture, squeezing the mixture from the middle to the edges. The denser mixture flows to the edges first. Due to the higher temperature around the edges, the mixture at the edges solidifies first. With multiple venting, the upper die head of the mold will be raised and lowered multiple times. After multiple squeezing of the mixture, the mixture will gradually flow from the middle to the edges. Combined with the fluid components in the formula, a gradient material is gradually formed.

[0046] (3) After demolding, place the gradient grinding blank into a curing oven for heating and curing. The heating and curing procedure is as follows: Maintain a curing temperature of 150℃ and a curing time of 2.5 hours; Then the temperature is increased from 150℃ to 180℃, and this heating process takes 60 minutes; Maintain a curing temperature of 180℃ and a curing time of 4 hours; The temperature was increased from 180℃ to 210℃, and the heating process took 60 minutes. Maintain a curing temperature of 210℃ and a curing time of 5 hours; The temperature was increased from 210℃ to 250℃, and the heating process took 60 minutes. Maintain a curing temperature of 250℃ and a curing time of 8 hours.

[0047] (4) Finally, the gradient abrasive is obtained by machining.

[0048] Example 2 (1) Preparation of raw materials for gradient abrasive friction material: Aromatic alcohol phenolic resin 12% 10% bismaleimide modified phenolic resin 12% Styrene-butadiene rubber 7% EPDM rubber Potassium hexatite whiskers 9% 6% sisal fiber 8% flake graphite 6% silica Hollow beads 4% Potassium feldspar 8% 7% diatomaceous earth 6% zeolite 5% dolomite A method for preparing a gradient abrasive includes the following steps: (1) Add aromatic phenolic resin, bismaleimide modified phenolic resin, styrene-butadiene rubber, ethylene propylene diene monomer rubber, flake graphite, silica, hollow cenospheres, potassium feldspar, diatomaceous earth, zeolite and dolomite into a high-speed mixer and mix for 25 minutes. Then add potassium hexatitanate whiskers and sisal fiber in proportion and mix for 22 minutes until uniform to obtain the mixture.

[0049] (2) The mixture and steel backing are placed in a porous mold. The temperature in the middle of the mold is 120℃, and the temperature around the mold is 135℃. The molding pressure is 20MPa. After the mold is closed and pressurized for 60s, the first venting is performed. The pressure is held for 75s for the second venting, then held for 60s for the third venting, then held for 45s for the fourth venting, then held for 30s for the fifth venting, and finally held for 17min to obtain a gradient grinding blank. The upper die head of the grinding blank mold is arc-shaped, high in the middle and low around the edges. When pressure is applied, the upper die head of the mold squeezes the mixture, squeezing the mixture from the middle to the edges. The denser mixture flows to the edges first. Due to the higher temperature around the edges, the mixture solidifies first. With multiple venting, the upper die head of the mold will be raised and lowered multiple times. After multiple squeezing of the mixture, the mixture will gradually flow from the middle to the edges. Combined with the fluid components in the formula, a gradient material is gradually formed.

[0050] (3) After demolding, place the gradient grinding blank into a curing oven for heating and curing. The heating and curing procedure is as follows: Maintain a curing temperature of 150℃ and a curing time of 2.5 hours; Then the temperature is increased from 150℃ to 180℃, and this heating process takes 60 minutes; Maintain a curing temperature of 180℃ and a curing time of 4.5 hours; The temperature was increased from 180℃ to 210℃, and the heating process took 60 minutes. Maintain a curing temperature of 210℃ and a curing time of 6 hours; The temperature was increased from 210℃ to 250℃, and the heating process took 60 minutes. Maintain a curing temperature of 250℃ and a curing time of 10 hours.

[0051] (4) Finally, the gradient abrasive is obtained by machining.

[0052] Example 3 (1) Preparation of raw materials for gradient abrasive friction material: 15% aromatic phenolic resin 11% bismaleimide modified phenolic resin 9% styrene-butadiene rubber 8% EPDM rubber Potassium hexatite whiskers 12% 7% sisal fiber 6% flake graphite 5% silica Hollow beads 5% Potassium feldspar 9% 5% diatomaceous earth 2% zeolite Dolomite 6% A method for preparing a gradient abrasive includes the following steps: (1) Add aromatic phenolic resin, bismaleimide modified phenolic resin, styrene-butadiene rubber, ethylene propylene diene monomer rubber, flake graphite, silica, hollow cenospheres, potassium feldspar, diatomaceous earth, zeolite and dolomite into a high-speed mixer and mix for 30 minutes. Then add potassium hexatitanate whiskers and sisal fiber in proportion and mix for 20 minutes until uniform to obtain a mixture.

[0053] (2) The mixture and steel backing are placed in a porous mold. The temperature in the middle of the mold is 150℃, and the temperature around the mold is 170℃. The molding pressure is 40MPa. After the mold is closed and pressurized for 60s, the first venting is performed. The pressure is held for 75s for the second venting, then held for 60s for the third venting, then held for 45s for the fourth venting, then held for 30s for the fifth venting, and finally held for 18min to obtain a gradient grinding blank. The upper die head of the grinding blank mold is arc-shaped, high in the middle and low around the edges. When pressure is applied, the upper die head of the mold squeezes the mixture, squeezing the mixture from the middle to the edges. The denser mixture flows to the edges first. Due to the higher temperature around the edges, the mixture at the edges solidifies first. With multiple venting, the upper die head of the mold will be raised and lowered multiple times. After multiple squeezing of the mixture, the mixture will gradually flow from the middle to the edges. Combined with the fluid components in the formula, a gradient material is gradually formed.

[0054] (3) After demolding, place the gradient grinding blank into a curing oven for heating and curing. The heating and curing procedure is as follows: Maintain a curing temperature of 150℃ and a curing time of 3 hours; Then the temperature is increased from 150℃ to 180℃, and this heating process takes 60 minutes; Maintain a curing temperature of 180℃ and a curing time of 5 hours; The temperature was increased from 180℃ to 210℃, and the heating process took 60 minutes. Maintain a curing temperature of 210℃ and a curing time of 5.5 hours; The temperature was increased from 210℃ to 250℃, and the heating process took 60 minutes. Maintain a curing temperature of 250℃ and a curing time of 9 hours.

[0055] (4) Finally, the gradient abrasive is obtained by machining.

[0056] Example 4 (1) Preparation of raw materials for gradient abrasive friction material: 10% aromatic phenolic resin 8% bismaleimide modified phenolic resin Styrene-butadiene rubber 8% 14% EPDM rubber Potassium hexatite whiskers 11% 10% sisal fiber 7% flake graphite 7% silica Hollow beads 2% Potassium feldspar 5% 6% diatomaceous earth 3% zeolite Dolomite 9% A method for preparing a gradient abrasive includes the following steps: (1) Add aromatic phenolic resin, bismaleimide modified phenolic resin, styrene-butadiene rubber, ethylene propylene diene monomer rubber, flake graphite, silica, hollow cenospheres, potassium feldspar, diatomaceous earth, zeolite and dolomite into a high-speed mixer and mix for 35 minutes. Then add potassium hexatitanate whiskers and sisal fiber in proportion and mix for 23 minutes until uniform to obtain the mixture.

[0057] (2) The mixture and steel backing are placed in a porous mold. The temperature in the middle of the mold is 180℃, and the temperature around the mold is 200℃. The molding pressure is 30MPa. After the mold is closed and pressurized for 60s, the first venting is performed. The pressure is held for 75s for the second venting, then held for 60s for the third venting, then held for 45s for the fourth venting, then held for 30s for the fifth venting, and finally held for 20min to obtain a gradient grinding blank. The upper die head of the grinding blank mold is arc-shaped, high in the middle and low around the edges. When pressure is applied, the upper die head of the mold squeezes the mixture, squeezing the mixture from the middle to the edges. The denser mixture flows to the edges first. Due to the higher temperature around the edges, the mixture at the edges solidifies first. With multiple venting, the upper die head of the mold will be raised and lowered multiple times. After multiple squeezing of the mixture, the mixture will gradually flow from the middle to the edges. Combined with the fluid components in the formula, a gradient material is gradually formed.

[0058] (3) After demolding, place the gradient grinding blank into a curing oven for heating and curing. The heating and curing procedure is as follows: Maintain a curing temperature of 150℃ and a curing time of 2 hours; Then the temperature is increased from 150℃ to 180℃, and this heating process takes 60 minutes; Maintain a curing temperature of 180℃ and a curing time of 5 hours; The temperature was increased from 180℃ to 210℃, and the heating process took 60 minutes. Maintain a curing temperature of 210℃ and a curing time of 6 hours; The temperature was increased from 210℃ to 250℃, and the heating process took 60 minutes. Maintain a curing temperature of 250℃ and a curing time of 10 hours.

[0059] (4) Finally, the gradient abrasive is obtained by machining.

[0060] The physical and mechanical properties of the gradient abrasive and non-gradient abrasives (comparative examples) prepared in the examples were tested according to the test methods of TB / T 3196-2015 "Synthetic Brake Shoes for Locomotives". The bonding strength of the back plate of the abrasive was tested according to the test methods of UIC541-4-2010 "Brakes - Brakes and Synthetic Brake Shoes - General Conditions for Certification of Synthetic Brake Shoes".

[0061] The preparation method of the non-gradient abrasive in the comparative example is as follows: The formulation of the comparative non-gradient abrasive is as follows: 12% aromatic phenolic resin, 16% nitrile rubber modified phenolic resin, 12% styrene-butadiene rubber, 10% EPDM rubber, 7% potassium hexatitanate whiskers, 9% sisal fiber, 5% flake graphite, 10% potassium feldspar, 3% diatomaceous earth, 5% zeolite, and 11% dolomite.

[0062] The formulation of the comparative example differs from that of Example 1 in that: silica and hollow celery beads are removed, and the bismaleimide modified phenolic resin is replaced with nitrile rubber modified phenolic resin. The mass contents of aromatic phenolic resin, nitrile rubber modified phenolic resin, styrene-butadiene rubber and dolomite are changed.

[0063] The preparation steps of the comparative non-gradient grinding tool are the same as those in Example 1, except that in step (2) of the preparation steps, the mold is heated from top to bottom during the pressing process. The mixture and steel back are placed into the porous mold, the mold temperature is 100°C, the forming pressure is 35MPa, no air is released, and the pressure is maintained for 16 minutes to obtain the grinding tool blank.

[0064] The results are shown in Table 1.

[0065] Table 1 Test values ​​of physical and mechanical properties of gradient abrasives As can be seen, the performance of the gradient abrasive gradually changes at different locations, with density and strength gradually increasing from the core to the edges, and the highest strength at the perimeter. The bonding strength between the gradient abrasive and the backing plate is also relatively high.

[0066] The frictional properties of the gradient abrasive and the comparative non-gradient abrasive were tested on a scaled-down test bench, and the results are shown in Table 2.

[0067] Table 2. Test values ​​of friction performance of the gradient grinder scaled-down table Compared to the comparative example, the gradient abrasive showed lower wear and a significantly longer service life. After the test, the surface of the gradient abrasive was normal, with no chipping or spalling.

[0068] The adhesion coefficients of the gradient abrasive and the comparative non-gradient abrasive were tested on a wheel-rail adhesion simulation test machine.

[0069] Test conditions: The wheel-rail adhesion coefficient of the gradient abrasive (Examples 1-4) and the comparative non-gradient abrasive were tested on a wheel-rail adhesion simulation tester under water medium conditions.

[0070] The adhesion coefficient of the comparative non-gradient abrasive is 0.18.

[0071] The adhesion coefficients of the gradient abrasives (Examples 1-4) ranged from 0.20 to 0.30, representing an improvement of 11% to 67% compared to the comparative examples. Specifically, the adhesion coefficient of Example 1 was 0.20, an improvement of 11% compared to the comparative examples; the adhesion coefficient of Example 2 was 0.25, an improvement of 39% compared to the comparative examples; the adhesion coefficient of Example 3 was 0.28, an improvement of 56% compared to the comparative examples; and the adhesion coefficient of Example 4 was 0.30, an improvement of 67% compared to the comparative examples. The results indicate that the gradient abrasives can significantly improve wheel-rail adhesion performance in aqueous media, and different degrees of improvement can be achieved by adjusting the abrasive parameters.

[0072] Wheel-rail shaping tests were conducted on a 1:1 scale grinding wheel shaping test machine, comparing gradient grinding wheels with a comparative non-gradient grinding wheel. The test conditions were: wheel speed 250 km / h, and the shaping time required to reduce the wheel surface roughness level from 30 dB to 15 dB for a 20-order polygonal wheel was used as the evaluation index.

[0073] Comparative non-gradient abrasive: shaping time was 4 h.

[0074] Gradient abrasive: The shaping time is 2-3 hours, and the shaping efficiency is improved by 25%-50% compared to the comparative example. Specific implementation data are as follows: Example 1: Shaping time 2.0 h, efficiency improved by 50%; Example 2: Shaping time 2.2 h, efficiency improved by 45%; Example 3: Shaping time 2.5 hours, efficiency improved by 38%; Example 4: Shaping time 3.0 h, efficiency improved by 25%.

[0075] The results show that the gradient grinder can significantly improve the shaping efficiency of 20th order polygonal wheels, and the efficiency improvement can be achieved by adjusting the grinder parameters by 25% to 50%.

[0076] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A gradient abrasive tribological material, characterized in that, It is prepared from the following components in the indicated mass percentages: Aromatic alcohol phenolic resin 9%-15% Bismaleimide modified phenolic resin 8%-13% Styrene-butadiene rubber 5%-12% EPDM rubber 7%-14% Potassium hexatite whiskers 7%-12% Sisal fiber 6%-10% Flake graphite 5%-8% 5%-10% silica Hollow bead floats 2%-6% Potassium feldspar 5%-10% Diatomaceous earth 3%-7% Zeolite 2%-6% Dolomite 5%-9%.

2. The gradient abrasive tribological material according to claim 1, characterized in that, The precipitated silica has a particle size of 10-50 nm; the hollow cenospheres have a particle size of 100-200 µm; and the zeolite has a density of 1.9-2.4 g / cm³. 3 Hardness 3-3.

5.

3. A method for preparing a gradient abrasive, characterized in that, Includes the following steps: S1. Add the component raw materials of the gradient grinding wheel friction material as described in claim 1 or 2 to a high-speed mixer and mix them to obtain a mixture; S2. Place the mixture and steel backing into the grinding die and press them to form a gradient grinding blank. S3. After demolding, the gradient abrasive blank is heated and cured, and finally machined to obtain the gradient abrasive. The steel backing serves to fix the friction material of the abrasive.

4. The method for preparing a gradient abrasive according to claim 3, characterized in that, In step S1, the specific process of preparing the mixture is as follows: aromatic phenolic resin, bismaleimide modified phenolic resin, styrene-butadiene rubber, EPDM rubber, flake graphite, silica, hollow cenospheres, potassium feldspar, diatomaceous earth, zeolite and dolomite are added to a high-speed mixer and mixed for 20-35 minutes according to the proportion. Then, potassium hexatitanate whiskers and sisal fibers are added according to the proportion and stirred for 20-25 minutes until uniform to obtain the mixture.

5. The method for preparing a gradient abrasive according to claim 3, characterized in that, In step S2, the specific process of compression molding is as follows: the mixture and steel backing are placed into the grinding die. The die is heated from top to bottom and from all sides. The temperature in the middle of the die is 100-180℃, and the temperature around the die is 120-200℃. The temperature around the die is higher than the temperature in the middle of the die. The molding pressure is 20-40MPa. After the die is closed and pressurized for 60s, the first venting is performed. The pressure is held for 75s for the second venting, then held for 60s for the third venting, then held for 45s for the fourth venting, then held for 30s for the fifth venting, and finally held for 16-20min to obtain the gradient grinding die blank.

6. The method for preparing a gradient abrasive according to claim 3, characterized in that, In step S2, during the molding process, the upper die head of the grinding die is arc-shaped, with a high center and low edges. When pressure is applied, the upper die head of the die squeezes the mixture from the center to the edges. The denser mixture flows to the edges first, and because the temperature is higher at the edges, the mixture at the edges solidifies first.

7. The method for preparing a gradient abrasive according to claim 3, characterized in that, In step S3, the specific process of heating and curing is as follows: after demolding, the gradient-grind blank is placed in a curing oven for heating and curing. The heating and curing procedure is as follows: Maintain a curing temperature of 150℃ and a curing time of 2-3 hours; Then the temperature is increased from 150℃ to 180℃, and this heating process takes 60 minutes; Maintain a curing temperature of 180℃ and a curing time of 4-5 hours; The temperature was increased from 180℃ to 210℃, and the heating process took 60 minutes. Maintain a curing temperature of 210℃ and a curing time of 5-6 hours; The temperature was increased from 210℃ to 250℃, and the heating process took 60 minutes. Maintain a curing temperature of 250℃ and a curing time of 8-10 hours.

8. The gradient abrasive prepared by the method according to any one of claims 3-7, characterized in that, The performance of the gradient abrasive gradually changes at different locations, with the density gradually increasing and the strength gradually increasing from the core to the edge.

9. The application of the gradient abrasive friction material according to claim 1 or 2, or the gradient abrasive according to claim 8, characterized in that, Used to prepare tread cleaning devices for high-speed rail and urban rail vehicles.

10. A tread cleaning device for high-speed rail and urban rail vehicles, characterized in that, It contains the gradient abrasive friction material as described in claim 1 or 2, or the gradient abrasive as described in claim 8.

Citation Information

Patent Citations

  • Grinding device of tread cleaning device for urban rail and preparation method thereof

    CN112810575A